Kurikulum Pendidikan Islam dalam Perspektif Hadits Tarbawi - Dinda Amanda Ainun Nuzul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
The curriculum has two meanings, in a narrow sense curriculumis a number of subjects taken by students in an educational institution, and in a broad sense curriculum is